2006
DOI: 10.1677/joe.1.06872
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of leptin and refeeding on the fasting-induced decrease of pituitary type 2 deiodinase and thyroid hormone receptor β2 mRNA expression in mice

Abstract: Profound changes in thyroid hormone metabolism occur in the central part of the hypothalamus-pituitary-thyroid (HPT) axis during fasting. Hypothalamic changes are partly reversed by leptin administration, which decreases during fasting. It is unknown to what extent leptin affects the HPT axis at the level of the pituitary. We, therefore, studied fasting-induced alterations in pituitary thyroid hormone metabolism, as well as effects of leptin administration on these changes. Because refeeding rapidly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
(39 reference statements)
0
20
0
3
Order By: Relevance
“…Chronic leptin treatment could also prevent the fall in T 4 determined by 70 h of fasting (3). On the other hand, other studies (11) have shown that leptin (20 g/0.5 ml twice a day) did not restore the decreased serum T 3 and T 4 in 24-h-fasted mice, despite serum leptin normalization. Lujan et al (31), using rhesus monkeys submitted to a prolonged dietary regimen, also observed that leptin infusion for 16 wk did not restore serum T 3 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Chronic leptin treatment could also prevent the fall in T 4 determined by 70 h of fasting (3). On the other hand, other studies (11) have shown that leptin (20 g/0.5 ml twice a day) did not restore the decreased serum T 3 and T 4 in 24-h-fasted mice, despite serum leptin normalization. Lujan et al (31), using rhesus monkeys submitted to a prolonged dietary regimen, also observed that leptin infusion for 16 wk did not restore serum T 3 .…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, further studies are needed in order to understand the influence of leptin on the thyroid axis during fasting and food restriction, which correspond to quite different physiological conditions. Boelen et al (11) showed that refeeding after 24 h of fasting in mice resulted in marked increase in serum leptin levels, which were not different compared with control mice; however, it did not result in a complete recovery of serum T 4 and T 3 levels. These results indicate that normalization of leptin levels does not always parallel restoration of serum thyroid hormone levels, suggesting that other peripheral signals may play a role in the regulation of thyroid gland economy during caloric deprivation.…”
Section: Discussionmentioning
confidence: 98%
“…In mice, fasting decreased the expression of D2 in the pituitary (41). It had been shown in rats that D2 activity and mRNA expression in BAT are up-regulated by insulin (19 -21), and more so in insulindeficient rats than in normal rats (21).…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have reported that icv leptin administered after a 48-hour fast restores the fasting-induced decrease of serum TSH in rats (46), suggesting a major role for downregulation of TRH expression in the PVN. However, there are probably additional factors independent from hypothalamic TRH, since leptin administration during or following fasting does not prevent the decrease in TSHb mRNA expression despite restored hypothalamic proTRH mRNA expression (47). In addition, a relatively short period of refeeding does not result in restored pituitary TSHb mRNA expression (47), while it is sufficient to restore hypothalamic NPY and POMC expression (48).…”
Section: Pituitarymentioning
confidence: 99%